Comparison of Chest Computed Tomography Findings in Patients with H1N1 and Coronavirus Disease-2019 Pneumonia - Sadullah Şimşek; Cihan Akgül Özmen (Gazi Medical Journal)
Objective: In this study, we compared the differences between high-resolution computed tomography (CT) features of two types of viral pneumonia associated with H1N1 virus and coronavirus disease-2019 (COVID-19). Methods: A total of 25 patients with H1N1 pneumonia were compared with 150 patients with COVID-19 pneumonia. The findings were analyzed by IBM SPSS Statistics for Windows, version 22 (IBM Corp., Armonk, N.Y., USA). CT findings were compared between groups by chi-square test, and scale variables were compared using the t-test. Finally, significant findings for the H1N1 or COVID-19 groups were evaluated by logistic regression analysis. Results: The median age of COVID-19 pneumonia patients was 54.6±15.9 years, and the median age of H1N1 pneumonia patients was 46.2±12.4 years (p<0.01). H1N1 pneumonia patients were younger than COVID-19 pneumonia patients. Based on the distribution pattern, diffuse pattern, peripheral pattern, and bronchopulmonary infiltration were observed more frequently in COVID-19 pneumonia (46.0%, 80.7%, 49.3%, respectively, p<0.05). Mediastinal lymphadenopathy and pleural effusion were observed more frequently in patients with H1N1 pneumonia (24% and 36%, respectively, p<0.05). Logistic regression analysis demonstrated that advanced age and a diffuse-peripheral pattern indicated COVID-19 (p=0.031, p=0.029). Conclusion: Most of the lesions caused by COVID-19 pneumonia are located in the peripheral region and near the pleura, whereas those caused by influenza virus pneumonia are far from the peripheral region.